Analiza mobilnosti dodiplomskih študentov na izbranih visokošolskih institucijah - Novak, Riko (Management, 2013)
The article explores the mobility of undergraduate students at three selected higher education institutions in three different countries. Students, who participated in the analysis, have been involved in mobility programmes over the last six years (between 2006 and 2011) at the following higher education institutions: Germany Duale Hochschule Baden Württemberg Karlsruhe, Norway University of Tromso and Slovenia Faculty of Management. The empirical research was conducted on a population of 3,539 undergraduate students, who completed part of their academic curriculum in the host country during the period under investigation. The purpose of this article was to examine the motivational factors inuencing the decision for an international mobility destination and the expectations of students on a sample of288 (mobile) undergraduates. The research has shown that the majority of students of the selected educational institutions chose mobility because of the international experience, that gender has an impact on the duration of a student mobility stay and that in the majority of cases the students are satised with the mobility program.
Keywords: knowledge; mobilnost; student; študenti; visokošolski študij; znanje